Can entrepreneurship be taught to young people with autism? A simulation of entrepreneurship for children with autism in Malaysia - Kurniawan, Yohan; Ijon, Ruzaini; Abd Latif, Siti Fathihah; Mohamed, Ateerah Abdul Razak; Rusdi, Fairuz A'dilah; Nik Azim, Nik Ahmad Farhan (Universitas Tangerang Raya, 2024)
Autism Spectrum Disorder (ASD) is a neurocognitive condition that is often seen in young children and impacts a variety of developmental elements, including impairments in social interaction, recurrence of certain behavioural patterns, and issues with verbal and non-verbal communication. These young people frequently struggle with self-management issues and need on the help of their family and communities. The individual is typically taught autonomous chores such as taking care of personal hygiene (bathing, cleaning equipment, etc.) and cleaning their living area by autism treatment centres, particularly in Malaysia. It's critical to acquire life skills, such as the capacity to work, in addition to one's capacity for self-management, to prevent becoming a burden to one's family and society. These other equally significant parts of life, such as entrepreneurial abilities, are not addressed. In order to build entrepreneurial skills and provide job experience for high-functioning autistic children, this project aims to create modules based on cognitive and psychomotor learning. It also conducts entrepreneurial simulations and tests the participants' knowledge of the field. The success of this entrepreneurship programme will be evaluated using observational and focus group discussion (FGD) approaches. The accompanying instructors and student volunteers will get training for trainers to ensure the success of this module. There are four sections to this module: Training for training, business simulation, business implementation, and effectiveness assessment are the first four steps. The expected outcome of this project is to create a module for high-functioning autistic young people that focuses on cognitive and psychomotor-based entrepreneurship abilities. Additionally, it is anticipated that this module will aid in preventing autism sufferers from experiencing long-term poverty, particularly those who belong to lower-income households.